Effects of total solids content on performance of sludge mesophilic anaerobic digestion and dewaterability of digested sludge. (April 2017) - An, Dong; Wang, Tianfeng; Zhou, Qi; Wang, Chaosheng; Yang, Qiyong; Xu, Bingjie; Zhang, Qingfang
Highlights: TS influence volumetric biogas production rate and ultimate biogas yield. NCST and TS of thickened sludge increased with increasing of initial TS. NCST was negative correlated with water removal efficiency by centrifugation. Abstract: The role of total solids (TS) content on sludge mesophilic anaerobic digestion (AD) was investigated in batch reactors. A range of TS below 10% was evaluated with two replicates. The volumetric biogas production rate (VBPR) increased with increasing initial TS. On day 5, VBPR increased from 133.2 ± 11.2 mL L −1  d −1 at TS 2% to 1111.7 ± 58.1 mL L −1  d −1 at TS 10%. The ultimate biogas yield ( P ) firstly increased and then decreased with the increasing TS. The greatest P was 246.8 mL g −1 -VSadded at TS 8%. The corresponding free ammonia nitrogen (FAN) and total ammonia nitrogen (TAN) were 84.0 ± 16.1 and 1163.0 ± 108.6 mg L −1, respectively. Normalized capillary suction time (NCST) and solid content of thickened sludge obtained by centrifuging sludge increased with increasing TS. On day 49, NCST were 1.2 ± 0.2 (TS = 2%) and 13.2 ± 1.1 (TS = 10%) s g −1 -TS. Meanwhile, solid content of thickened sludge was 7.5 ± 0.5 (TS = 2%) and 15.4 ± 0.0% (TS = 10%). In summary, high VBPR and dewatering effects were obtained after TS content optimization.